Respuesta :

4.b.

Answer:  See below.

Step-by-step explanation:

For the equation f(x) = 2x

3.a.  f(6) means use x = 6 in the equation f(x) = 2x

so f(6) would be f(6)= 2(6)

f(6) = 12

3.b.  f(-11) = 2(-11)

f(-11) = -22

3.c.  f(2.75) = 2(2.75)

f(2.75) = 5.5

3.d.  This is turned around.  We are told f(x)=20, so what would x need to be for f(x) to be 20?  Since f(x) = 2x, we can say 20 = 2x.  Therefore x = 10

f(10) = 20

The rest of (3) are solved in the same fasion.h

For the equation  f(x)= 5x+50

4.a.  f(7) = 5(7)+50

f(7) = 85

4.b. f(-12)

  f(-12) = 5*(-12)+50

f(-12) = -60

Continue in the same fashion for these types of problems.